Risk Factors for Developing Cardiovascular Disease in The next 10-Years in Type 2 DM - Praphasil, Orawan; Boontein, Pannipa (Journal of The Royal Thai Army Nurses, 2025)
This descriptive correlational study aimed to identify factors that may predict cardiovascular risk over the next decade in 144 individuals with type 2 diabetes attending internal medicine outpatient departments and diabetes clinics at two hospitals. The data collection comprised retrospective blood test results from the preceding six months, along with measurements of body weight, height, waist circumference, and blood pressure. Additionally, responses to questionnaires were gathered, addressing general information, pertinent health history, self-management behaviors for diabetes, and 10-year cardiovascular risk assessment. Descriptive statistics and logistic regression analysis were employed for data analysis The results indicated that the mean 10-year cardiovascular risk was 17.10%, with 33.33% of patients categorized as low risk and 66.67% as high risk. Significant factors associated with elevated 10-year cardiovascular risk, as opposed to low risk (p < .05), encompassed age, systolic blood pressure, duration of diabetes, and cholesterol levels. Individuals aged over 65 years (OR = 69.71, 95%CI = 7.90–616.19, p < .05) and those with systolic blood pressure exceeding 140 mmHg (OR = 8.33, 95%CI = .78–89.52, p < .05) were significant predictors of cardiovascular risk. The model was able to account for 75% of the variance in 10-year cardiovascular risk.